Cyber Public Private Partnership ICS/SCADA and Critical Infrastructure Protection Strategic Vision (Journal of The Colloquium for Information Systems Security Education, 2016)
Since 2003 cyberspace has become a significant national asset for the United States and our elements of national power: Diplomacy, Informational, Military and Economic (DIME). The global balance of power is now shaped by a new multi-polar diffusion of power, disruptive technologies and Moore’s law of technology advancement [1]. These factors have enabled cyberspace Advanced Persistent Threats (APT) which include; criminal networks, nation states, terrorist organizations and others, to develop leveling strategies against the United States national strengths; however, early in the Internet’s development the focus was on access and ease of connection, not security. Cyberspace today now hosts and underwrites the global economic market worth trillions of dollars. The United States is critically unprepared for a massive disruption of our critical infrastructure from a cyberattack. APTs (Nation states and non-state actors) have identified and continue to map critical vulnerabilities in each of our national critical infrastructure sectors: chemical, communications, commercial facilities, critical manufacturing, dams, energy, defense industrial base, emergency services, financial, food and agriculture, healthcare and public health, nuclear (reactors, materials and waste), transportation, water and waste water systems, information technology, and government facilities--and have demonstrated intent and capability to disrupt them in case of an international conflict or crisis. The nation lacks a comprehensive and executable strategy to effectively respond [2] Several major factors contribute the nation’s unpreparedness. For one, the nation is critically short of cyber security professionals to meet the demand for national cyber defense. For another, Federal government agencies and US policy/laws inadequately prepare, coordinate, share and integrate public and private capabilities to defend the U.S. from a massive cyber disruption.